Analysis Simulation of LTE Network Capacity in Pekanbaru - Sari, Linna Oktaviana (International Journal of Electrical, Energy and Power System Engineering, 2018)
In Indonesia, LTE technology is appropriately to be applied by telecommunication operators in improving cellular communication services. In 2018, the number of LTE network users in Pekanbaru continues to increase. Increasing number of customers need increasing service capacity. To fulfill the capacity needs of LTE network services with better signal level in 2018, then in this study has been analyzed the simulation of LTE network capacity in Pekanbaru City. In this research, we use Monte Carlo simulation for analyze capacity. Frequency Division Duplex method with 1800 MHz frequency and COST- 231 Hata propagation model were used in the simulation. The results of simulation capacity in Pekanbaru show that the urban area needs 143 number of BTSs for 20MHz bandwidth, BTSs coverage reaches 84.4% of covered area and highest focus zone covered at -100 dbm signal, and for 5MHz Bandwidth, the total number of subscribers is 47.375, with 39.158 connected subscribers and 8.216 unsuccessful subscribers.